Sociodemographic profile of women who underwent tubal ligation: an integrative literature review (Research, Society and Development, 2021)
Tubal ligation consists of mechanical occlusion or partial resection of the fallopian tubes, at the same time that the junction of the gametes cannot occur, eliminating the chances of fertilization. This method is among the preference of couples when they opt for contraceptive practice, both in developed and developing countries. This study is based on the following guiding question: What is the socio-demographic profile of women who underwent tubal ligation? Therefore, the aim of this study is to analyze the socio-demographic profile of women who underwent tubal ligation through an integrative literature review study. This is a review, through scientific productions from the database: Latin American Literature in Health Sciences – LILACS, Scientific Electronic Library Online – SCIELO, Virtual Health Library – VHL, of the last 5 years, that is, from 2015 to 2020. Among women with 3 or more children, tubal ligation was the most frequent practice, although it was surpassed by the use of injectable hormones in the 20 to 29 age group. Therefore, this research opened new possibilities to deepen the knowledge about tubal ligation and the variables related to women who choose this procedure. This reality highlights the need to implement health education measures as well as strategies focused on this audience, as regrets and consequences are part of this process, as highlighted in the selected studies.